Rhoptry and Dense Granule Secreted Effectors Regulate CD8+ T Cell Recognition of Toxoplasma gondii Infected Host Cells - Rommereim, Leah M.; Fox, Barbara A.; Butler, Kiah L.; Cantillana, Viviana; Taylor, Gregory A.; Bzik, David J. (Frontiers in Immunology, 2019)
Toxoplasma gondii secretes rhoptry (ROP) and dense granule (GRA) effector proteins to evade host immune clearance mediated by interferon gamma (IFN-), immunity-related GTPase (IRG) effectors, and CD8+ T cells. Here, we investigated the role of parasite-secreted effectors in regulating host access to parasitophorous vacuole (PV) localized parasite antigens and their presentation to CD8+ T cells by the major histocompatibility class I (MHC-I) pathway. Antigen presentation of PV localized parasite antigens by MHC-I was significantly increased in macrophages and/or dendritic cells infected with mutant parasites that lacked expression of secreted GRA (GRA2, GRA3, GRA4, GRA5, GRA7, GRA12) or ROP (ROP5, ROP18) effectors. The ability of various secreted GRA or ROP effectors to suppress antigen presentation by MHC-I was dependent on cell type, expression of IFN-, or host IRG effectors. The suppression of antigen presentation by ROP5, ROP18, and GRA7 correlated with a role for these molecules in preventing PV disruption by IFN--activated host IRG effectors. However, GRA2 mediated suppression of antigen presentation was not correlated with PV disruption. In addition, the GRA2 antigen presentation phenotypes were strictly co-dependent on the expression of the GRA6 protein. These results show that MHC-I antigen presentation of PV localized parasite antigens was controlled by mechanisms that were dependent or independent of IRG effector mediated PV disruption. Our findings suggest that the GRA6 protein underpins an important mechanism that enhances CD8+ T cell recognition of parasite-infected cells with damaged or ruptured PV membranes. However, in intact PVs, parasite secreted effector proteins that associate with the PV membrane or the intravacuolar network membranes play important roles to actively suppress antigen presentation by MHC-I to reduce CD8+ T cell recognition and clearance of Toxoplasma gondii infected host cells.